Phytochemical Investigation of Lepionurus sylvestris Blume and Their Anti-Diabetes Effects via Anti-Alpha Glucosidase and Insulin Secretagogue Activities Plus Molecular Docking - Sathianpong Phoopha; Surat Sangkaew; Chatchai Wattanapiromsakul; Wanlapa Nuankaew; Tong Ho Kang; Sukanya Dej-adisai (MDPI AG, 2023)
This study presents a phytochemical investigation of Lepionurus sylvestris leaf extracts and their anti-diabetic activities. Traditionally, L. sylvestris leaves were used as vegetables and food in local recipes, but the root extracts of the plant can also be used in body tonic and erectile dysfunction treatments. Following a preliminary anti-diabetic activity screening test, the 80% ethanolic leaf extract exhibited potent anti-alpha glucosidase activity. So, the leaves' active components were selected for further investigation. Firstly, the plant was extracted via maceration using lower to higher polarity solvents such as hexane, ethyl acetate, ethanol, and water, respectively, to obtain the four crude extracts. Then, the phytochemicals contained in this plant were investigated via classical column chromatography and spectroscopy techniques. Anti-diabetic activity was evaluated via anti-alpha glucosidase and insulin secretagogue assays. The results showed that five compounds were isolated from the fractionated ethanolic leaf extract: interruptin A; interruptin C; ergosterol; diglycerol; and 15-16-epoxy-neo-cleoda-3,7(20),13(16),14-tetraene-12,17:18,19-diolide, a new diterpene derivative which is herein referred to as lepionurodiolide. Interruptin A and the new diterpene derivative exhibited the greatest effect on anti-alpha glucosidase activity, showing IC50 values of 293.05 and 203.71 μg/mL, respectively. Then, molecular docking was used to study the sites of action of these compounds. The results showed that interruptin A and the new compound interacted through H-bonds with the GLN279 residue, with a binding energy of −9.8 kcal/mol, whereas interruptin A and C interacted with HIS280 and ARG315 a with binding energy of −10.2 kcal/mol. Moreover, the extracts were investigated for their toxicity toward human cancer cells, and a zebrafish embryonic toxicity model was used to determine herbal drug safety. The results indicated that ethyl acetate and hexane extracts showed cytotoxicity to both Hela cells and human breast adenocarcinomas (MCF-7), which was related to the results derived from using the zebrafish embryonic toxicity model. The hexane and ethyl acetate presented LC50 values of 33.25 and 36.55 μg/mL, respectively, whereas the ethanol and water extracts did not show embryonic toxicity. This study is the first of its kind to report on the chemical constituents and anti-diabetic activity of L. sylvestris, the leaf extract of which has been traditionally used in southern Thailand as a herbal medicine and food ingredient.